THE INFLUENCE OF PERSONAL SOCIAL CULTURAL AND PSYCHOLOGY TOWARD PURCHASING DECISION SAMSUNG CELLPHONE - Wartoyo Hadi; Golda Farida (STIE Binaniaga, 2017)
The purpose of this study was to investigate: the influence of social, cultural, psychological variables toward purchasing decision Samsung Cellphone on Oke Shop Bogor partially and simultaneously. The method used in this study was multiple regression. The result of this study was: partially, there are positive influence between social, cultural, personal, and psychological variables toward purchasing decision Samsung Cellphone on Oke Shop Bogor. The independent variable that influenced the most toward purchasing decision Samsung Cellphone is cultural variable. In the other hand, simultaneously using correlation product moment technique can be concluded that there is a positive strong and significant correlation.Keywords : social, cultural, personal, psychological, and purchasing decision.